Combined Reconstructive Surgery after Complex Hand Injuries: Clinical Case and Review of Literature - Kurlavičius, Domas; Rauba, Gediminas; Stundžaitė-Baršauskienė, Giedrė (Lietuvos chirurgija, 2021)
The article deals with one of the most complex hand injuries in the practice of plastic and reconstructive surgery – amputation of degloving the upper tissues of the upper limb. The clinical case of a woman who has suffered from this trauma, the course of treatment, remote functional and aesthetic results are presented.